The Production of Salted-Egg With Low Levels of Sodium and Cholesterol - Ilyas, Syafruddin; It Jamilah; Nursal (International Journal of Ecophysiology, 2023)
The specific aim to be achieved is the production of salted eggs low-sodium and low cholesterol. Spices for making 30 salted duck eggs are coconut fiber ash 1 kg, green tea in two tablespoons, 15 gram of bay leaves, 15 gram of reed root, 15 gram of leaves of mahkota dewa, 15 gram guava leaves, and 1/2 kg palm sugar. The method in the experiment is a complete randomized method with five treatment groups namely; five treatments (days) and five replications. K = first day, P1 = fourth day, P2 = eighth day, P3 = twelfth day, P4 = sixteenth day. The main ingredients are duck eggs taken randomly and used as research samples. Each treatment consisted of five duck eggs. The parameters measured in each treatment (observation day) were organoleptic tests, cholesterol and sodium content from salted eggs. The results obtained were salted egg organoleptic test, cholesterol content in salted eggs, and better sodium content in salted eggs at the incubation until day 14